2010
DOI: 10.1002/jhm.594
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding talent: A lesson from industry on embracing physician workforce challenges

Abstract: Disclosure: Nothing to report.Shortages of both generalist and specialist physicians are intensifying as the US healthcare system confronts an unprecedented confluence of demographic pressures, including an aging population, the retirement of thousands of babyboomer physicians, the growth of nonpractice opportunities for MDs, and physician demands for greater work-life balance. This work posits that the medical profession might benefit from recognizing how progressive nonmedical companies systematically approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
0
6
0
11
Order By: Relevance
“…The timing of physician retirement is particularly salient for patient care continuity and transitions of care in hospital enterprises where mentors of the younger hospitalist workforce may be scarce [17]. As for the age at which most physicians retired, we found that the majority retired later than the traditional retirement age of [65].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The timing of physician retirement is particularly salient for patient care continuity and transitions of care in hospital enterprises where mentors of the younger hospitalist workforce may be scarce [17]. As for the age at which most physicians retired, we found that the majority retired later than the traditional retirement age of [65].…”
Section: Discussionmentioning
confidence: 78%
“…Physician retirement planning can create challenges when retirement or death inevitably occurs, because hospitals and medical institutions often find it difficult to replace experienced, older physicians and to facilitate knowledge transfer [17]. The career progression of a growing pool of younger physicians waiting in the wings for professional opportunities can also be impeded without individual physician and institutional hospital succession plans in place [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Die Studienlage belegt jedoch, dass Höchstleistungen im Beruf und in Führungspositionen bis in das hohe Alter hinein möglich sind [7,23,24,25,30,37,40,53,56]. Für die Klinik ist vielmehr das biologische Alter (Fitness) wichtig.…”
Section: Einfluss Des Alters Auf Die Leistungsfähigkeitunclassified
“…B. Eltern-und Pflegezeit). Schließlich ist auch das individuelle Altersgefühl von Bedeutung, das wiederum davon abhängt, wie der Mitarbeiter vom Unternehmen im Hinblick auf sein Alter behandelt wird [23,24,25,30,37,40]. Hier zeigt sich, dass Motivation, Fähigkeiten und Erfahrungen die Leistungsfähigkeit "der Älteren" über die "der Jüngeren" hinaus verbessern kön-nen [7,23,24,25,30,37,40,53,56].…”
Section: Einfluss Des Alters Auf Die Leistungsfähigkeitunclassified
See 1 more Smart Citation